Experimental Investigation of EDM Parameters on Machining Si3N4-TiN Conductive Ceramic Composite Using Hallow Tube Electrode for Improving Geometrical Accuracy. (2018) - Selvarajan, L.; Mouri, P.; Ramesh Raja, R.
Abstract: This paper presents the outcome obtained by the experimental studies that are carried out to conduct an investigation on the effect of electrical discharge machining processes (EDM) input parameters on the characteristics of output process parameters. Electrical discharge machining process, which enables to machine hard and high temperature metals and alloys like super alloys, carbides, ceramics, composites, heat resistant alloys. Ceramic matrix composites (CMC), possesses High-temperature strength, creep resistance, chemical resistance, low porosity, and low density. However, these materials are difficult to process due to the need of application of large cutting force and high cost on tool consumption. EDM presents negligible machining force and acceptable tooling cost is a potential non-traditional machining technique for machining CMC. Silicon Nitrite-Titanium Nitrite (Si3 N4 -TiN) composites finds its application on engineering components, cutting tools, crucible for molten metal. The designed full factorial procedure was used to perform the experiment. The optimal parameters for machining Si3 N4 -TiN composites using hollow tube electrode was studied through this work. The experiment carried out was with the discharge current, pulse on and off time, dielectric pressure and servo speed. Relative output parameters were circularity, cylindricity, perpendicularity, top radial overcut, bottom radial overcut, and taper angle. The experiment conducted were based on the Taguchi L25 Orthogonal Array (OA). The predicted data which was obtained by RSM is used to find the parameter which influences the output in major. Optimum process parameters to achieve the desired EDM efficiency, less tool wear rate, maximum metal removal rate (MRR), circularity while machining Si3 N4 -TiN composite material can be obtained by utilizing the results derived through this experiment.